Hubungan Bullying dengan Gangguan Tidur pada Mahasiswa Semester Satu Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Sri Ratna Dewi; I Wayan Eka Arsana; Putu Galih Mia Utami (Aesculapius Medical Journal, 2022)
Violence in the form of bullying is still rife even at the university level today. Students who are victims of bullying will have an impact on mental health to cause disruption of sleep patterns. This study was conducted to determine the correlation between bullying and sleep disorders in first semester students of the Faculty of Medicine and Health Sciences, Warmadewa University. This research is an analytical study with a cross-sectional design. Implementation in November – December 2021 with a simple random sampling method. The data analysis used was univariate, bivariate, and multivariate analysis. The final result of multivariate analysis showed p value < 0.05 (0.005) with an OR value of 3.5 which means there is a relationship between the incidence of bullying and sleep disorders and students who experience bullying have a 3.5 times greater chance of experiencing sleep disturbances than university students. who did not experience bullying after controlling for the gender variable. Students are expected to be able to participate in preventing bullying in the high school area and further researchers are expected to add other factors that influence the relationship between bullying and sleep disorders.